2021
DOI: 10.3390/electronics10101165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhancement on Deep Learning Based Hepatic Vessel Segmentation

Abstract: Colorectal cancer (CRC) is the third most common type of cancer with the liver being the most common site for cancer spread. A precise understanding of patient liver anatomy and pathology, as well as surgical planning based on that, plays a critical role in the treatment process. In some cases, surgeons request a 3D reconstruction, which requires a thorough analysis of the available images to be converted into 3D models of relevant objects through a segmentation process. Liver vessel segmentation is challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…We observe that abundant blood vessels are available on tissue surfaces and can be extracted as a new set of image features. In this paper, two types of blood vessel features are proposed for endoscopic images: branching points and branching segments [10]. Two novel methods, ridgenessbased circle test and ridgeness-based branching segment detection are presented to extract branching points and branching segments, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…We observe that abundant blood vessels are available on tissue surfaces and can be extracted as a new set of image features. In this paper, two types of blood vessel features are proposed for endoscopic images: branching points and branching segments [10]. Two novel methods, ridgenessbased circle test and ridgeness-based branching segment detection are presented to extract branching points and branching segments, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, liver vessel segmentation is still challenging due to the varying and complicated vessel structure [3]. Image-related challenges also increase the difficulty of liver vessel segmentation, including diverse contrast between the vessel and surrounding tissues and images with a low-quality [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another objective is to facilitate feature extraction and other subsequent tasks such as detection and segmentation of critical structures [24,25]. It has been reported that the performance of segmentation and detection in medical images can be augmented by employing effective pre-processing techniques on low-contrast images [20,30,17,4].…”
Section: Introductionmentioning
confidence: 99%